2015
DOI: 10.1016/j.jeurceramsoc.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Micropillar compression inside zirconia degraded layer

Abstract: In the dental field, Yttria-doped Tetragonal Polycrystalline Zirconia (Y-TZP) plays an important role due to its high mechanical properties, good aesthetics and bio-inert behavior. Surface mechanical properties are crucial for Y-TZP especially when it comes to osseointegration or contact loading, since it may undergo a spontaneous aging phenomenon when exposed to humid environment, creating a thin degraded layer that affects surface integrity. In this work, polished samples of Y-TZP have been artificially aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The observed behavior is completely different for micropillars extracted from the monoclinic surface layer that forms on 3Y-TZP after hydrothermal degradation, which present extensive microcracking, as was reported in a previous work [47]. The slope of the linear part of loading curves in monoclinic degraded micropillars is less than half that of non-cracked tetragonal micropillars, due to the large population of orientated microcracks at the grain boundaries.…”
Section: Loading-unloading Tests At Increasing Peak Stressmentioning
confidence: 45%
See 1 more Smart Citation
“…The observed behavior is completely different for micropillars extracted from the monoclinic surface layer that forms on 3Y-TZP after hydrothermal degradation, which present extensive microcracking, as was reported in a previous work [47]. The slope of the linear part of loading curves in monoclinic degraded micropillars is less than half that of non-cracked tetragonal micropillars, due to the large population of orientated microcracks at the grain boundaries.…”
Section: Loading-unloading Tests At Increasing Peak Stressmentioning
confidence: 45%
“…The slope of the linear part of loading curves in monoclinic degraded micropillars is less than half that of non-cracked tetragonal micropillars, due to the large population of orientated microcracks at the grain boundaries. Even though the unloading slope at the peak stress in loadingunloading tests of degraded micropillars also increased slightly with the peak stress, the slope change was associated to the variation in load-transfer area due to the closure of increasing fractions of cracks under the applied stress [47].…”
Section: Loading-unloading Tests At Increasing Peak Stressmentioning
confidence: 92%
“…The area of the hysteresis loop tends to increase as stress and strain both increase. The appearance of hysteresis loops may be attributed to reverse transformation and reopening of closed pores in the flash-sintered 3YSZ 49 . The pillar after the cyclic loading test experiences 1% plastic strain, but still does not exhibit cracks as can be seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is a key challenge with these materials. Practical SMCs are therefore most likely to involve small specimen length scales and few grains [6,24,25], so that when the transformation happens it is unconstrained and the transformation mismatch is accommodated at free surfaces. Lai et al [6] first showed that in small zirconia micropillars with very few grains (i.e., oligocrystals or single crystals), the mismatch stresses associated with the transformation could be relieved at the pillar surfaces, permitting recoverable strains as high as ~7-8%.…”
Section: Introductionmentioning
confidence: 99%